Dining & Death: interdisciplinary perspectives on the 'Funerary Banquet' in ancient art, burial and belief - Oxford Classics, Archaeology and Somerville College (Oxford Classics, Archaeology and Somerville College, 2010)
The conference brought together scholars from multiple disciplines (Classical Archaeology, Sinology, Egyptology, Ancient Near Eastern Archaeology) in order to explore the varied forms and meanings of banqueting imagery in tomb paintings and sculptures, with a particular focus on the relationship between the images and beliefs about death. The ultimate aims were to compare forms and meanings of the images, as well as approaches and interpretations prevailing in the different disciplines represented.